Senam Genggam Jari untuk Penurunan Tekanan Darah Penderita Hipertensi di Desa Bogoarum kecamatan Plaosan Kabupaten Magetan - Devita Anugrah Anggraini; Didit Damayanti; Priyoto Priyoto (jurnal ABDIMAS Indonesia, 2025)
High blood pressure is a problem that is widely suffered by the community, especially in Indonesia. Hypertension that is not detected early and treated properly can trigger coronary heart disease, heart failure, stroke, chronic kidney failure, blindness due to hypertensive retinopathy and peripheral arterial disease. The purpose of community service is to lower blood pressure in people with hypertension. It is hoped that through this activity it will be a source of information to increase the knowledge of people with hypertension about finger grip gymnastics techniques to lower blood pressure. The implementation method in this community service is to carry out finger grip gymnastics activities and before the activity, blood pressure measurements are carried out. This community service activity was carried out on people with hypertension aged >40 years as many as 36 elderly people at the Posyandu, Bogoarum Village, Plaosan District, Magetan Regency, East Java Province. The results of the blood pressure of people with hypertension who participated in finger grip gymnastics obtained pretest blood pressure with a mean blood pressure value of 157.78 / 92.22 mmhg. While the posttest blood pressure with a mean blood pressure value of 145 / 83.3 mmhg. It was concluded that there was a decrease between the pretest and posttest blood pressure values. This service is expected to be a preventive recommendation that can be given to hypertension sufferers, namely so that the community remains active in participating in finger grip gymnastics activities that can be done routinely at the integrated health post so that it can reduce the number of hypertension complications.